p120-catenin subfamily members have distinct as well as shared effects on dendrite morphology during neuron development in vitro - Donta, Maxsam S.; Srivastava, Yogesh; Di Mauro, Christina M.; Paulucci-Holthauzen, Adriana; Waxham, M. Neal; McCrea, Pierre D. (Frontiers in Cellular Neuroscience, 2023)
Dendritic arborization is essential for proper neuronal connectivity and function. Conversely, abnormal dendrite morphology is associated with several neurological pathologies like Alzheimer’s disease and schizophrenia. Among major intrinsic mechanisms that determine the extent of the dendritic arbor is cytoskeletal remodeling. Here, we characterize and compare the impact of the four proteins involved in cytoskeletal remodeling–vertebrate members of the p120-catenin subfamily–on neuronal dendrite morphology. In relation to each of their own distributions, we find that p120-catenin and delta-catenin are expressed at relatively higher proportions in growth cones compared to ARVCF-catenin and p0071-catenin; ARVCF-catenin is expressed at relatively high proportions in the nucleus; and all catenins are expressed in dendritic processes and the soma. Through altering the expression of each p120-subfamily catenin in neurons, we find that exogenous expression of either p120-catenin or delta-catenin correlates with increased dendritic length and branching, whereas their respective depletion decreases dendritic length and branching. While increasing ARVCF-catenin expression also increases dendritic length and branching, decreasing expression has no grossly observable morphological effect. Finally, increasing p0071-catenin expression increases dendritic branching, but not length, while decreasing expression decreases dendritic length and branching. These distinct localization patterns and morphological effects during neuron development suggest that these catenins have both shared and distinct roles in the context of dendrite morphogenesis.